mcevoy's handbook of photovalitaics fundamentals and applications - soteris a. kalogirau (academic press an imprint of elsevier, 2018)
mcevoy's handbook of photovoltaics, third edition, is a benchmark publication for those involved in the design, manufacture, and use of these devices